2(x+3)+6x=3(9-x)

Simple and best practice solution for 2(x+3)+6x=3(9-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)+6x=3(9-x) equation:


Simplifying
2(x + 3) + 6x = 3(9 + -1x)

Reorder the terms:
2(3 + x) + 6x = 3(9 + -1x)
(3 * 2 + x * 2) + 6x = 3(9 + -1x)
(6 + 2x) + 6x = 3(9 + -1x)

Combine like terms: 2x + 6x = 8x
6 + 8x = 3(9 + -1x)
6 + 8x = (9 * 3 + -1x * 3)
6 + 8x = (27 + -3x)

Solving
6 + 8x = 27 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6 + 8x + 3x = 27 + -3x + 3x

Combine like terms: 8x + 3x = 11x
6 + 11x = 27 + -3x + 3x

Combine like terms: -3x + 3x = 0
6 + 11x = 27 + 0
6 + 11x = 27

Add '-6' to each side of the equation.
6 + -6 + 11x = 27 + -6

Combine like terms: 6 + -6 = 0
0 + 11x = 27 + -6
11x = 27 + -6

Combine like terms: 27 + -6 = 21
11x = 21

Divide each side by '11'.
x = 1.909090909

Simplifying
x = 1.909090909

See similar equations:

| 6+5-4x=1-4 | | 4=2(z-8) | | -6d=-5d+7 | | -n-4=-2n+6 | | 16(x-4)=8(x-8) | | 3(u+-2)=0 | | -15+m=39 | | -5j=8-3j | | 81x^2+72x+9=0 | | 5x+4=3x+21 | | 9w-4w+3=13 | | v-14=-7 | | 5(7x-3)=42 | | 3n=5n-32 | | -8k+3k=15 | | x-(0.1x)=2500 | | f(x)=3x-cos(5X) | | -k+3k=15 | | 3k-7+7k=31-24k-5 | | y^2+30y+216= | | -4+5b=39 | | 8+3G=5g | | 1.4x+2.6=-8.1 | | 7(x+8)=4(x-6) | | -7(x+2)-7=-14x+7(x+4) | | 2x+5yforx=3y=9 | | 3v-7=-4v+7 | | -6s=-5s-10 | | 3(x-5)=4(x+8) | | x-14+2x+5=0 | | -u-9=-2u | | 10x-15=13x-20 |

Equations solver categories